2021
DOI: 10.1177/1534735420977697
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Effects of CAM Techniques on Inflammation and Emotional States: An Integrative Single-Case Study on a Breast Cancer Survivor

Abstract: Background: This study on a breast cancer survivor investigated how episodic practice of various complementary and alternative medicine (CAM) techniques affected the dynamics of emotional states and urinary neopterin—an inflammation marker. Methods: The 49-year-old female patient (diagnosis: ductal breast carcinoma 5 years before study start, suffering from chronic fatigue and depression) collected her entire urine in 12-hour intervals (from about 8 a.m. to 8 p.m. and from about 8 p.m. to 8 a.m.) for 28 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 48 publications
0
17
0
1
Order By: Relevance
“…This integrative single-case study is part of a larger project on breast cancer survivors that examines the effects of emotionally meaningful incidents on stress system activity. Various results dealing with this patient have already been published (22,23,35,36).…”
Section: Methodsmentioning
confidence: 94%
See 4 more Smart Citations
“…This integrative single-case study is part of a larger project on breast cancer survivors that examines the effects of emotionally meaningful incidents on stress system activity. Various results dealing with this patient have already been published (22,23,35,36).…”
Section: Methodsmentioning
confidence: 94%
“…Moreover, some increases in urinary IL-6 levels occurred in advance, i.e., up to 108-120 h (-lag 10, energy healing) or 120-132 h (-lag 11, physiotherapy) (Figures 2A-E), suggesting that the patient responded immunologically in anticipation of CAM practice. Indeed, weekly interviews revealed that several CAM techniques, such as energy healing, physiotherapy and choir rehearsals, had been planned by the patient days or even weeks in advance [see (23) for further details]. Concentration changes of stress system parameters in anticipation of the actual occurrence of an incident have repeatedly been found in integrative single-case studies (25,28,29).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations